Barrier-enforcing measures as treatment principle in allergic rhinitis: a systematic review. (June 2014) - Andersson, Morgan; Greiff, Lennart; Ojeda, Pedro; Wollmer, Per
Abstract Background and objectives Barrier-enforcing measures have been suggested as treatment options for allergic rhinitis. This review identifies and describes the literature on the subject. Methods Relevant publications were searched for in the PubMed database (search entries: 'allergic rhinitis' and 'treatment'). The evaluation comprised condition (seasonal or perennial allergic rhinitis), type of intervention, duration of treatment, study design, peer review status or not, number of test subjects, type of allergen exposure, and outcome in terms of effects or not on nasal symptoms of allergic rhinitis. Results Fifteen studies were either identified in the PubMed database search or from the reference lists of identified publications. Seven were placebo-controlled, randomized, and peer-reviewed, and symptom-reducing effects were reported by all of these reports. Limitations of this review reflect that the remainder of the studies had inferior designs, particularly lack of placebo control. Conclusions Barrier-enforcing measures as achieved by nasal administrations of cellulose powder and microemulsions, respectively, have symptom-reducing effects in allergic rhinitis.